Penerapan Restorative Justice dalam Kasus Kekerasan Domestik di Indonesia: Studi Empiris di Wilayah Perkotaan dan Pedesaan - Karisma, Dian; Pratiwi , Berliant; Handoko, Sri (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Domestic violence is a critical issue affecting many individuals and families in Indonesia, with varied impacts across urban and rural areas. This study examines the implementation of the Restorative Justice approach in resolving domestic violence cases in these contexts and identifies factors influencing its effectiveness. Using a mixed-methods approach, the research combines quantitative analysis through surveys and qualitative insights from in-depth interviews. Data were collected from 300 respondents, including victims, offenders, and mediators, from urban and rural settings, alongside interviews with key stakeholders. The findings reveal significant differences in acceptance and satisfaction with Restorative Justice processes between urban and rural populations. In urban areas, higher legal awareness and access to trained mediators contribute to a 70% satisfaction rate, reflecting better participation and understanding of the process. In contrast, rural areas exhibit a lower satisfaction rate of 50%, hindered by cultural norms, limited legal knowledge, and a shortage of qualified mediators. Despite these challenges, Restorative Justice shows promise in addressing domestic violence by fostering dialogue, accountability, and reconciliation, emphasizing victim empowerment and offender rehabilitation. This study underscores the necessity of adapting Restorative Justice practices to local socio-cultural contexts to enhance effectiveness. Recommendations include developing tailored mediator training programs, increasing public awareness, and integrating community leaders into the process to build trust and legitimacy. The research contributes to the discourse on legal reform by highlighting the potential of Restorative Justice to create a more inclusive, responsive, and sustainable mechanism for resolving domestic violence cases in Indonesia. These findings are pivotal for policymakers in designing adaptive strategies to bridge the urban-rural divide and strengthen the justice system.